Bacterial contamination on used face masks among nursing home healthcare personnel. Issue 1 (15th March 2023) - Nightingale, Madison; Mody, Manali; Rickard, Alexander H.; Cassone, Marco
Abstract: Objectives: Since the beginning of the COVID-19 pandemic, face masks have been worn by many in public areas and for prolonged periods by healthcare workers (HCWs). This may facilitate bacterial contamination and transmission to and from patients in nursing homes where clinical care areas with strict precautions and residential and activity areas are interconnected. We assessed and compared bacterial mask colonization in HCWs belonging to different demographic categories and professions (clinical and nonclinical) and among HCWs who had worn the mask for different periods of time. Design, setting and participants: We conducted a point-prevalence study of 69 HCW masks at the end of a typical work shift in a 105-bed nursing home serving postacute care and rehabilitation patients. Information collected about the mask user included profession, age, sex, length of time the mask was worn, and known exposure to patients with colonization. Results: In total, 123 distinct bacterial isolates were recovered (1–5 isolates per mask), including Staphylococcus aureus from 11 masks (15.9%) and gram-negative bacteria of clinical importance from 22 masks (31.9%). Antibiotic resistance rates were low. There were no significant differences in the number of clinically important bacteria among masks worn more or less than 6 hours, and there were no significant differences among HCWs with different job functions or exposure to colonized patients. Conclusions: Bacterial mask contamination was not associated with HCW profession or exposure and did not increase after 6 hours of mask wearing in our nursing home setting. Bacteria contaminating HCW masks may differ from those colonizing patients.